Pengamanan Audio Rindik Bali Menggunakan Metode Least Significant Bit Berbasis Android - Agung Jayanti, I Gusti Ayu Mirah; Cahyadi Putra, I Gusti Ngurah Anom; Widiartha, I Made; Karyawati, Anak Agung Istri Ngurah Eka; Suhartana, I Ketut Gede Suhartana Gede; Sanjaya ER, Ngurah Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 2 (2022): JELIKU Volume 11 No 2, November 2022, 2022)
The development of an increasingly fast era makes the pace of technology is also growing which is directly proportional to the level of crime that is growing as well. Dissemination of personal or group information becomes vulnerable to attacks from other parties, so the security of data or confidential information needs to be improved. Bali has many different musical instruments in each region, both in terms of the name and the instrument itself. One of them is Rindik. Rindik is one of the percussion instruments that ’ s still in demand because of its distinctive sound (Aristana et al., 2015). Because of Balinese Rindik is still interesting for most peoples, making its need to be secured to avoid digital crime so that the owner of the audio feels safe. One of the many security that can avoid an action crime on Balinese Rindik musical instruments is by inserting text containing personal data from the audio owner in the format (.txt) into Balinese Rindik audio in the format (.wav) using the Least Significant Bit (LSB) steganography method.